The Effect of Slalom Dribble Training on the Dribbling Skill - Bahtra, Ridho; Annas, Moch. (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
The problem of this study is the low dribbling skill of the SSB Putra Painan soccer players in Pesisir Selatan Regency. This study aims to identify the effect of slalom dribble training towards the dribbling skill of the SSB Putra Painan soccer players in Pesisir Selatan Regency. This study is a quasi exsperimental with one group pre test-post test design. The population in this study is 53 SSB Putra Painan soccer players in Pesisir Selatan Regency. The sampling technique used is purposive sampling which covers 20 players aged 10 to 12 years old. The data collecting technique used is testing with dribbling skill test as an instrument. The data analysis and hypothesis testing used is the comparison analysis technique by using T-test with significance level of ÃŽÂ±=0.05. From the data analysis result, it can be concluded that there is an effect of slalom dribble training towards dribbling skill of the SSB Putra Painan soccer players in Pesisir Selatan Regency, with the T-test coefficient tcount (8.73) is greater than ttable (1.729)